Development Tolerance in Early Childhood: Management and Practices for Emancipatory Curriculum - Jumiatmoko; Siti Wahyuningsih; Upik Elok Endang Rasmani; Bambang Winarji; Anjar Fitrianingtyas; Nurul Shofiatin Zuhro; Novita Eka Nurjanah (Jurnal Pendidikan Anak Usia Dini Undiksha, 2024)
Tolerance is key to realizing ECEfS (Early Childhood Education for Sustainability). However, the implementation of the Merdeka Curriculum presents new challenges in developing tolerance in early childhood education, particularly due to differences in children's socio-cultural backgrounds and limited variety of stimulating activities.This study aims to identify the dynamics of tolerance development management in PAUD institutions implementing the Kurikulum Merdeka. The research employs a Case Study method, which is suitable for answering "how" research questions. A qualitative approach is used with interactive analysis based on the model of Miles, Huberman, and Saldana (2012). Data were collected through observations, in-depth interviews, and document studies, then analyzed to identify management processes, implementation categories, and encountered challenges. Score justification was used to measure the effectiveness of implementation in the components of planning, organizing, actuating, and controlling in relation to the Capaian Pembelajaran Fase Pondasi (CPFP) and the Capaian Fase Profil Pelajar Pancasila (CFP3). The findings indicate that tolerance development management in PAUD follows a cyclical process, yet its effectiveness remains in the moderate category (average score of 2.2). The main challenges identified include the diversification of stimulation activities and differences in children's socio-cultural backgrounds. The study's implications highlight the need for improving teacher competence, strengthening collaboration with parents, and innovating play-based activities to optimize tolerance development in early childhood education.